The sliding set-point: how insulin and diet interact to explain the obesity epidemic (and how to fix it). Issue 5 (October 2018) - Gower, Barbara A.; Goss, Amy M.
Abstract : Purpose of review: The current approach to weight loss (intentional energy deficit) is difficult to implement and sustain, and rarely leads to successful long-term weight loss maintenance. The aim of this article is to review recent literature on the role of insulin in obesity propensity, and by extension, the effectiveness of carbohydrate restriction in facilitating weight loss, with particular attention to individual variability in patient response. Recent findings: A genetic signature for insulin secretion predisposes to elevated BMI. A genetic signature for insulin resistance is a marker for impaired fat storage, is associated with relative leanness, and predisposes to cardiometabolic disease. The largest randomized weight-loss trial ever conducted to examine insulin/diet interactions revealed no interactive effect of insulin phenotype with diet composition on body weight in the context of energy restriction. However, smaller studies revealed unique effects of carbohydrate restriction on energy partitioning that are not reflected in body weight; that is, preferential loss of total and ectopic adipose tissue. Carbohydrate-restricted diets are associated with greater adherence, and with greater total and resting energy expenditure. Summary: For patients with a predisposition to high insulin secretion, carbohydrate restriction may facilitate long-term reductions in body fat, perhaps by reducing hunger, maintaining energy expenditure, and promoting adherence.